2021
DOI: 10.1080/21655979.2021.1960775
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate biomarkers correlated with poor prognosis of breast cancer based on bioinformatics analysis

Abstract: Breast cancer (BC) is a malignancy with high incidence among women in the world. This study aims to screen key genes and potential prognostic biomarkers for BC using bioinformatics analysis. Total 58 normal tissues and 203 cancer tissues were collected from three Gene Expression Omnibus (GEO) gene expression profiles, and then the differential expressed genes (DEGs) were identified. Subsequently, the Gene Ontology (GO) function and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway were analyzed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 94 publications
(104 reference statements)
2
20
0
Order By: Relevance
“…Others have shown that overexpression of CDC20 indicates unfavorable prognosis and poor response to endocrine therapy in ER + breast cancer (Alfarsi et al, 2019;Tang et al, 2019); in contrast, we discovered that CDC20 was related to worse prognosis only in the TNBC subtype, and we think that the different datasets that we analyzed result in the inconsistency. Other genes such as BUB1, NUF2, CDC20, ASPM, KIF2C, and PRC1 have biological relevance to breast cancer progression, and PLK1, NDC80, and CCNB2 only to TNBC progression, and these genes predict worse prognosis (Wang et al, 2015;Tang et al, 2019;Yang et al, 2019;Lv et al, 2020;Ren et al, 2020;Chen et al, 2021;Jiang et al, 2021;Koyuncu et al, 2021); likewise, we also found that these genes correlated negatively with prognosis in the TNBC subtype. Moreover, it is also reported that high expression levels of AURKB, CDC6, and ECT2 suggest a poor prognosis for breast cancer (Mahadevappa et al, 2017;Daulat et al, 2019;Huang et al, 2019;Xiu et al, 2019), whereas we only found that CDC6 was negatively positively related to overall survival, and we consider that it is also the different datasets and analysis methods that cause the disparity.…”
Section: Discussionsupporting
confidence: 72%
“…Others have shown that overexpression of CDC20 indicates unfavorable prognosis and poor response to endocrine therapy in ER + breast cancer (Alfarsi et al, 2019;Tang et al, 2019); in contrast, we discovered that CDC20 was related to worse prognosis only in the TNBC subtype, and we think that the different datasets that we analyzed result in the inconsistency. Other genes such as BUB1, NUF2, CDC20, ASPM, KIF2C, and PRC1 have biological relevance to breast cancer progression, and PLK1, NDC80, and CCNB2 only to TNBC progression, and these genes predict worse prognosis (Wang et al, 2015;Tang et al, 2019;Yang et al, 2019;Lv et al, 2020;Ren et al, 2020;Chen et al, 2021;Jiang et al, 2021;Koyuncu et al, 2021); likewise, we also found that these genes correlated negatively with prognosis in the TNBC subtype. Moreover, it is also reported that high expression levels of AURKB, CDC6, and ECT2 suggest a poor prognosis for breast cancer (Mahadevappa et al, 2017;Daulat et al, 2019;Huang et al, 2019;Xiu et al, 2019), whereas we only found that CDC6 was negatively positively related to overall survival, and we consider that it is also the different datasets and analysis methods that cause the disparity.…”
Section: Discussionsupporting
confidence: 72%
“…BRCA is recognized as one of the most frequent malignancies, which is the leading cause of cancer deaths in women (Bray et al, 2018). Despite the advances in early screenings and medical therapies, the prognosis of BRCA patients remains disappointing because of drug resistance (Chen et al, 2021). Thus, developing the novel biomarkers and exploring the molecular pathogenesis of BRCA for improving the diagnosis and prognosis of this disease is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…At present, surgery, chemotherapy, radiotherapy, and hormone therapy are available approaches for BRCA treatment (Liu and Ye, 2017). Despite rapid improvement in target therapy methods, the prognosis is still unsatisfactory due to drug resistance and recurrence (Chen et al, 2021). Immunotherapy has emerged as a revolutionary strategy in various tumors, but whether this method would represent a role in BRCA treatment is an open question (de la Cruz-Merino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The functions of AURKA in regulating mitosis, spindle composition and centrosome have been well researched [ 37 ]. In addition, studies have reported that AURKA from the serine/threonine kinase family was overexpressed in various cancers and can be used as a prognostic marker for breast cancer and advanced serous ovarian cancer [ 38 , 39 ]. Consistent with previous research, in the present study, AURKA showed a high expression in the DLBCL tissues and DLBCL cells, suggesting that AURKA may play a significant role in the DLBCL.…”
Section: Discussionmentioning
confidence: 99%